2020
DOI: 10.1039/c9tb01599j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a supramolecular hydrogel made of phospholipids and oleic acid with a high water content

Abstract: Formation of a structured lipid hydrogel able to accommodate a high amount of water (95%) without needing gelling agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…These q values correspond to Bragg’s distances of 8.0 nm, 2.6 nm, and 1.7 nm, respectively. These q and d-spacing values are in line with data reported by Talló et al [ 19 , 20 ] for the same HG but without the incorporation of AA. The shape of the scattering profile is typical of a scattering form factor corresponding to uncorrelated bilayers.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These q values correspond to Bragg’s distances of 8.0 nm, 2.6 nm, and 1.7 nm, respectively. These q and d-spacing values are in line with data reported by Talló et al [ 19 , 20 ] for the same HG but without the incorporation of AA. The shape of the scattering profile is typical of a scattering form factor corresponding to uncorrelated bilayers.…”
Section: Resultssupporting
confidence: 92%
“…Our research group has reported several studies regarding lipid materials and skin applications. The latest research is a complete characterization study of a new hydrogel (HG) invention, including a patent reported by K. Talló [ 17 , 18 , 19 , 20 ], and a characterization and skin permeation study of a new biocompatible lipid-based bigel (BG) reported by Loza-Rodríguez et al [ 21 ]. The HG is a colloidal lipid gel formed by aggregation of lipid vesicles under dilute conditions and without requiring gelling agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3B) as already observed for phospholipids. 31 For the latter, the matrix of the hydrogel seems to be formed by the closely packed structures of multilamellar vesicles as already reported in our recent publication. 18 For GlcB(OH)-4 , TEM showed several micrometer-long semi-rigid helical nanofibers with a uniform lateral diameter (17 ± 1 nm) close to the lateral arrangement of four GlcB(OH)-4 molecules (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…As for hydrogel Aiming to obtain hydrogels and micro-/nanoparticles with various properties made from different materials requires preparation using several methods. As for hydrogel preparation, physical crosslinking and chemical crosslinking are the main methods, including the freeze-heating cycle [73], Schiff-based reaction [74], and Michael addition [75]. To prepare microparticles, methods such as propylene carbonate emulsification-extraction [76], the membrane emulsification technique [77], liquid jet breakup [78], the electrostatic microdroplet method [79], spray drying, and chemical crosslinking [80] are used by researchers.…”
Section: The Preparation and Main Properties Of The Micro-/nanoparticle Hybrid Hydrogel Platformmentioning
confidence: 99%